Integrated network pharmacology and serum metabolomics approach deciphers the anti-colon cancer mechanisms of Huangqi Guizhi Wuwu Decoction - Pan, Boyu; Xia, Yafei; Fang, Senbiao; Ai, Jun; Wang, Kunpeng; Zhang, Jian; Du, Chunshuang; Chen, Yuzhou; Liu, Liren; Yan, Shu (Frontiers in Pharmacology, 2022)
Huangqi Guizhi Wuwu Decoction (HGWD), as a classic Chinese herbal decoction, has been widely used in treating various diseases for hundreds of years. However, elucidating its mechanisms-of-action remains a great challenge to the field. Through the network pharmacology approach, we discovered a potential use of HGWD in colon cancer (CC) treatment. The subsequent in vivo assay showed that orally administered HGWD markedly inhibited the growth of CC xenografts in mice. The enrichment analyses of core therapeutic targets revealed that HGWD affected the biological processes involved in CC cell proliferation, including metabolic reprogramming, apoptosis as well as immune regulation, while inhibiting cell survival-related signaling pathways, including MAPK and PI3K-Akt pathways. Notably, these virtual results were experimentally verified. Meanwhile, our results based on serum metabolomics showed that HGWD played a key anti-CC role in tumor-bearing mice via lipid metabolic pathways, including fatty acid biosynthesis and cholesterol metabolism, and that cytochrome P450 family 2 subfamily E member 1 (CYP2E1) is a potential therapeutic target. Together, our integrated approach successfully explained the polypharmcological mechanisms underlying the efficacy of HGWD on treating CC, providing a valuable insight into developing strategies to predict and interpret the therapeutic mechanisms of Chinese herbal decoctions.